Pengaruh Green Perceived Quality Dan Green Brand Image Terhadap Green Trust Dan Green Purchase Intention Pada Produk Micellar Cleansing Water Garnier - Hartanti, Anita; Aqmala, Diana; Anomsari, Ariati; Safitri, Maria (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to determine the effect of green perceived quality and green brand image on green trust and green purchase intention on Garnier Micellar Cleansing Water products. The population of this study were active Management students of Dian Nuswantoro University. The sample used was 70 respondents. The sampling technique used was the probability sampling technique, cluster random sampling type obtained from distributing questionnaires. The type of data used was primary data. The collected data will be analyzed through SEM-PLS with SmartPLS software version 3, including validity tests, reliability tests, R-square and path coefficients. The results of the study stated that green perceived quality and green brand image have a significant effect on green trust. This means that product quality and brand image that are considered environmentally friendly by consumers are important factors in increasing trust in environmentally friendly products. Green perceived quality does not have a significant effect on green purchase intention, this shows that green perceived quality in Garnier micellar cleansing water does not influence consumers enough to buy environmentally friendly products offered. While green brand image and green trust have a significant effect on green purchase intention, meaning that if consumers have a brand image and trust in environmentally friendly products, it will affect the purchase interest of the product. For the mediation effect, it shows that green trust is stated to be able to mediate or become an intermediary for green perceived quality significantly towards green purchase intention. While green brand image does not have a significant effect on green purchase intention through green trust, this shows that green trust so that the intervening variable in this study is stated to be unable to mediate the effect of green brand image on green purchase intention.